Biocontrol and Biostimulant Effect of a Fungal-Derived Extract in Commercial Varieties of Strawberry (Fragaria x ananassa Duch.) - Hael Conrad, Verónica (2022)
Objective: Strawberry postharvest fruits and plants are mainly affected by the fungus Botrytis cinerea (B. cinerea), which causes grey mould rot. Biological control agents and biostimulants can effectively control this fungus and promote plant growth. This study aimed to evaluate the capacity of a novel fungal-derived extract called culture filtrate (CF) to biocontrol grey mould rot in postharvest strawberries and plants while promoting plant growth.Methods: The CF extract was obtained from the liquid culture of a strawberry pathogenic fungus, gauzefiltered and inactivated by autoclave. The Fragaria x ananassa cultivars Camino Real, Benicia, and Merced were used. For the postharvest assay, fruit natural decay was evaluated by simulating real storage conditions. For the phytopathological assays, first-generation plants inoculated with B. cinerea were evaluated 26 days post infection. The effect of CF on plant growth and biomass promotion was evaluated 60 days post treatment (DPT).Results: The treatment with CF yielded healthier fruits of the three varieties, which presented minorseverity of grey mould symptoms compared to the controls treated with water or potato dextrose broth (PDB) by 7 DPT. For instance, 40% of Camino Real, 80% of Benicia, and 20% of Merced fruits presented an incipient lesion (severity 1), whereas no fruits treated with water or PDB showed this minor level of infection. On the contrary, around 50% and 70% of the control fruits presented the highest level of severity. Moreover, CF pre-treatment of Benicia “mother plants” protected first-generation untreated plants. Likewise, the best biostimulant effect was observed for Benicia plants, which presented an increased number of leaves and runner production 60 DPT.